Retinoic Acid Inducible Gene 1 Protein (RIG1)‐Like Receptor Pathway Is Required for Efficient Nuclear Reprogramming. (27th March 2017) - Sayed, Nazish; Ospino, Frank; Himmati, Farhan; Lee, Jieun; Chanda, Palas; Mocarski, Edward S.; Cooke, John P.
Abstract : We have revealed a critical role for innate immune signaling in nuclear reprogramming to pluripotency, and in the nuclear reprogramming required for somatic cell transdifferentiation. Activation of innate immune signaling causes global changes in the expression and activity of epigenetic modifiers to promote epigenetic plasticity. In our previous articles, we focused on the role of toll‐like receptor 3 (TLR3) in this signaling pathway. Here, we define the role of another innate immunity pathway known to participate in response to viral RNA, the retinoic acid‐inducible gene 1 receptor (RIG‐1)‐like receptor (RLR) pathway. This pathway is represented by the sensors of viral RNA, RIG‐1, LGP2, and melanoma differentiation‐associated protein 5 (MDA5). We first found that TLR3 deficiency only causes a partial inhibition of nuclear reprogramming to pluripotency in mouse tail‐tip fibroblasts, which motivated us to determine the contribution of RLR. We found that knockdown of interferon beta promoter stimulator 1, the common adaptor protein for the RLR family, substantially reduced nuclear reprogramming induced by retroviral or by modified messenger RNA expression of Oct 4, Sox2, KLF4, and c‐MYC (OSKM). Importantly, a double knockdown of both RLR and TLR3 pathway led to a further decrease in induced pluripotent stem cell (iPSC) colonies suggesting an additive effect of both these pathways on nuclear reprogramming. Furthermore, in murine embryonic fibroblasts expressing a doxycycline (dox)‐inducible cassette of the genes encoding OSKM, an RLR agonist increased the yield of iPSCs. Similarly, the RLR agonist enhanced nuclear reprogramming by cell permeant peptides of the Yamanaka factors. Finally, in the dox‐inducible system, RLR activation promotes activating histone marks in the promoter region of pluripotency genes. To conclude, innate immune signaling mediated by RLR plays a critical role in nuclear reprogramming. Manipulation of innate immune signaling may facilitate nuclear reprogramming to achieve pluripotency. Stem Cells 2017;35:1197–1207 Abstract : Abstract Video Link:https://www.youtube.com/watch?v=L4LO4jEuRhs&feature=youtu.be